The use of gabions as a tool for ecological engineering - Seath, Jessica Lauren (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Anthropogenic activities are centred in coastal ecosystems, including the development of harbours and/or marinas. The artificial structures used in coastal development typically has a different composition, orientation and level of complexity to that of natural ecosystems contributing to loss of biodiversity and increased incidence of invasive species. Ecological engineering research is attempting to identify different types of structures and materials that can increase species diversity and target species of conservation concern in coastal systems. The aim of this study was to investigate the efficacy of gabions (rock filled structures) as an ecological engineering tool by comparing community structure on these structures with pre-existing seawall structures within a small harbour and marina in South Africa (Knysna Harbour). The objectives of the study were to compare the differences in; 1) fish and; 2) colonising organisms' diversity and composition between two artificial structures. Thirteen gabion boxes were deployed in Knysna Harbour and together with corresponding seawalls, monitored quarterly over a period of 12 months (August 2020 "“ August 2021) to assess taxon and functional richness, diversity, abundance and composition of fish, invertebrate and algal species. Physico-chemical characteristics of the water body were also monitored quarterly. Remote underwater video systems were used to quantify MaxN (maximum number of a fish species in the frame at any one time during each set that gives an indication of relative abundance) and identify fish species. The results of the two-way crossed ANOVAs indicated that gabion habitats recruited greater numbers and more types of fish species and from more functional groups than the seawalls, especially omnivorous and carnivorous fish. Additionally, photoquadrats were used to quantify percentage cover, counts and to identify colonising taxa. The results of the two-way crossed ANOVAs indicated that gabions hosted greater numbers of species resulting in a higher overall diversity and abundance of colonising organisms than seawalls. By contrast, the seawalls supported more types of functional groups of colonising organisms than gabions, largely due to abundances of different algal species. The results from the crossed PERMANOVAs indicated that the composition of fish and colonising organisms were vastly different from one another, and that each habitat was supporting very different functional groups. Results indicate that whilst both gabions and seawalls contain several alien species, that the ratio of native to alien species is higher in gabion habitats. Additionally, this research observed that gabion structures hosted four species listed on the IUCN Red List of Threatened Species. This study has highlighted that the use of gabions (with their natural increased complexity) could be important to consider for the future of urban coastal development in harbours such as in Knysna Harbour. Ecological engineering projects using gabions have the potential to be used in South Africa in projects that aim at increasing biodiversity in urban coastal environments. As well as increasing the settlement and abundance of habitat-forming ecosystem engineers to ensure the long-term stability of these ecosystems. They can be used both in the development of new costal development projects as well as in an ad-hoc fashion where they can be interspersed on seawalls in harbours. Additionally, gabions have the potential to be used in projects that target species of conservation concern such as the endangered Knysna Seahorse (Hippocampus capensis). It is, however, important to monitor the invasion by non-native species in future ecological engineering projects in South Africa as well as their potential for creating ecological traps (a situation in which an organism may be convinced to settle in a low-quality habitat) for certain species.
Keywords: Ecological engineering -- South Africa Knysna Lagoon; Gabion; Barrier structure; Coastal zone management; Coastal engineering; Estuarine health -- South Africa Knysna Lagoon; Estuarine animals Monitoring -- South Africa Knysna Lagoon